Anthropometric Study of Nose Parameters in Iraqi Arabic and Kurdish Subjects (Possible Personal Identification Tool) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background and Purpose: The human nose has been reported to differ in its anatomy and morphologybetween different racial and ethnic groups. Nasal anthropometric features when studied can provide usefulinformation for reconstruction or esthetic surgical procedures and personal identification for forensicpurposes. Method: A total of 311 subjects with age (19-23) years were divided according to gender, race(Arabic or Kurdish), and residence regions in Iraq (north, middle and south). Different nose parameterswere measured for the subjects using digital Vernier caliper. Results: Comparing races, the nose heightand nose length were significant between Arab and Kurds, nasal index showed (60, 60.6) for Arabic vs.Kurdish, respectively. Sexual dimorphism was significant in all the parameters obtained. The fine nose wasthe commonest among all subjects. Parameters analysis revealed high positive significant correlation amongvarious parameters except the nasal index that showed negative correlation with nasal height and length.Conclusions: Nasal morphometric parameters were unique for each person and have variations betweendifferent race (Arabic and Kurdish), gender variation and the correlation among various parameters beenrecorded for Iraqi people. These morphometric evaluations are the key for standardization among Iraqis, andin comparison with different countries, this have great values in anatomical, surgical (aesthetic) and forensicaspects regarding personal identification.
Keywords: anthropometry, nasal dimension, nasal index, personal identification, Rhinoplasty